Realizing the American Dream: Parent Involvement and Racial Identity Development as It Correlates to Academic Achievement - Witherspoon, Sebastian L. (My University, 2013)
Students of color in America are failing to meet state academic standards at historic rates. This issue has recently gained significant attention due to what is being referred to as the achievement gap. Based on the No Child Left Behind Act, the achievement gap is defined as the disparity in academic performance between groups of students. When broken down to certain geographical areas these realities can be examined at a much deeper and personal level. In an effort to positively impact the achievement gap, this research is conducted in a state that has repeatedly failed in educating students of color in America, specifically African American & American Indian boys. Two of the perceived major contributors for the lack of academic success among students of color are researched. It is widely believed that lack of parent involvement and racial identity development awareness are significantly contributing to the achievement gap. This research is centered in Duluth, Minnesota at East High School. This school has traditionally been a White-American institution. It has become a broad belief that parent involvement creates higher levels of academic success. This research examines the correlation between knowing oneself as it pertains to racial identity development and the need to implement parent involvement programs within schools. A combination of both will undoubtedly result in higher levels of academic success and ultimately help students realize their American dream. This research shows the effects of implementation of racial identity development and parent involvement programs at East High School.
Keywords: East High School; students of color; No Child Left Behind Act; Educational Administration; Educational Leadership; American Indian; Duluth; achievement gap; African American; Minnesota